2015
DOI: 10.4236/psych.2015.63026
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Attention-Deficit/ Hyperactivity Disorder among Primary School Students in an Iranian Rural Region

Abstract: This study investigated the prevalence of attention-deficit/hyperactivity disorder (ADHD) in a rural population in Birjand, south east Iran. The total population of elementary students in this region was 3408. A random sample method selected 1381 children (727 boys, and 654 girls; mean of age = 8.2 years, SD = 1.5 years). Conners Rating Scales and Diagnostic and the Statistical Manual for Mental Disorders (DSM-IV-TR) were used for screening and diagnosis of ADHD. Ninety-nine students (7.2% of the students) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Regarding gender, this study found significantly higher prevalence of ADHD among boys (14.5) than girls (3.6). This is consistent with results reported by studies conducted in Egypt 11,15,16,18 , Iran 20,21 , Iraq 22 and China. 23 On the other hand, studies conducted in Qalyobia 14 and Alexandria 17 (Egypt) found no significant differences between prevalence of ADHD among males and females.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding gender, this study found significantly higher prevalence of ADHD among boys (14.5) than girls (3.6). This is consistent with results reported by studies conducted in Egypt 11,15,16,18 , Iran 20,21 , Iraq 22 and China. 23 On the other hand, studies conducted in Qalyobia 14 and Alexandria 17 (Egypt) found no significant differences between prevalence of ADHD among males and females.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present research showed a higher ADHD prevalence rate in boys than in girls which isconsistent with the findings of previous studies. 10,[15][16][17][18] However, the ADHD prevalence rate in the present study was higher than previous studies, 5,9,15,17,18 but was consistent with Meysamie's research. 16 The difference in findings of the present research and the previous ones can be attributed to geographical location and ADHD measurement tools, which may have caused these variations.…”
supporting
confidence: 89%
“…A review study which was carried out on the previous studies, estimated ADHD prevalence in pre-school boys in Ahvaz-Iran using the Conners scale and the results showed that the prevalence rate was 24.06 per cent, 4.51 per cent, 17.29 per cent and 2.25 per cent based on the positive rating scale, parent form, only teacher questionnaire and both parent and teacher questionnaires. 9 Moreover, a study was carried out on 1083 preschool children aged 5 and 6 years to estimate the prevalence of ADHD in Mashhad-Iran. Their result showed that 12.3 per cent of children suffer from ADHD and this was obtained after carrying out screening process using parent and teacher report using 10-items of Conners Index questionnaire and the Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS) clinical interview.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADHD is one of the most common childhood-onset psychiatric disorders. It develops in childhood and later becomes apparent in the preschool and early school years (Alizadeh, Armio, Coolidge, Flores, & Sutton, 2015; Cheng & Myers, 2005; Hamed, Taha, Sabra, & Bella, 2008; Kaur, Patidar, Meenakshi, Girdhar, & Kaur, 2014; Rutter & Taylor, 2002; Suvarna & Kamath, 2009; Tashakori & Afkandeh, 2011). It can be described as over activity, persistent and debilitating inattention, and impulsivity.…”
mentioning
confidence: 99%